The electrical resistivity structure of lithosphere across the Dharwar craton nucleus and Coorg block of South Indian shield: Evidence of collision and modified and preserved lithosphere. Issue 10 (9th October 2015) - Abdul Azeez, K. K.; Veeraswamy, K.; Gupta, Arvind K.; Babu, Narendra; Chandrapuri, Sateesh; Harinarayana, T.
Abstract: Magnetotelluric‐derived two‐dimensional lithospheric resistivity structure of the western Dharwar craton (WDC) and adjoining Coorg block indicates isolated low‐resistivity zones in the crust and three striking upper mantle conductive features within the highly resistive Archean lithosphere. The crustal conductors in the WDC show good spatial correlation with the exposed supracrustal rocks conformable with the relic schist belt channels having conductive mineral grains. Conductive zones within the Coorg crust might be related to the relatively young (933 Ma) metamorphic processes in the area and/or possible fluids derived from the Cretaceous passage of Reunion plume in the proximity of Coorg area. A near‐vertical conductive structure extending from the lower crust into the upper mantle coincides with the transition zone between Coorg and WDC. This is interpreted as the suture zone between the two tectonic blocks and provides evidence for the individuality of the two Archean terrains. An anomalous upper mantle conductive zone found beneath the craton nucleus may indicate a modified cratonic lithosphere. This could have been derived due to the collision between Coorg and WDC and possibly survived by the subsequent multiple episodes of melt and fluid infiltration processes experienced in the region. Thick (~190 km) and preserved lithosphere is mapped at the eastern segment of WDC. Resistive lithosphere of ~125 km thickness is imaged for the Coorg block. Key Points: Resistivity structure across the Dharwar craton and Coorg block of South India Magnetotelluric study infers mantle suture zone between the two tectonic blocks Anomalous conductive zone beneath craton nucleus indicates modified lithosphere